The use of thermally expandable microcapsules for increasing the toughness and heal structural adhesives - Chiaki Sato; Guillaume Pesquet; Lucas F. M. da Silva (Fracture and Structural Integrity)
In this research, the effect of thermally expandable microcapsules (TEMs) on mode I fracture toughness of structural adhesives were investigated. The single-edge-notch bending (SENB) test was used. Firstly, a standard toughness test was performed on adhesives with microcapsules. Secondly, since TEMs start their expansion at approximately 60ºC, the next specimens were fatigue tested expecting a local heating in the notch leading to the desired expansion before being statically loaded for fracture toughness determination. Thirdly, a manual local heating at 90ºC was applied in the notch before the fracture static test. The experimental results were successfully cross-checked through a numerical analysis using the virtual crack closure technique (VCCT) based on linear elastic fracture mechanics (LEFM). The major conclusion is that fracture toughness of the modified adhesives increased as the mass fraction of the TEMs increased.